Model-based Filtering of Interfering Signals in Ultrasonic Time Delay Estimations - Bächle, Matthias (Forschungsberichte aus der Industriellen Informationstechnik, 2023)
This work presents model-based algorithmic approaches for interference-invariant time delay estimation, which are specifically suited for the estimation of small time delay differences with a necessary resolution well below the sampling time. Therefore, the methods can be applied particularly well for transit-time ultrasonic flow measurements, since the problem of interfering signals is especially prominent in this application.